¿Viaje voluntario o deportación del rey Riroroko en 1897? Política de deportación en Pascua: 1897-1916 - Rolf Foerster (Nuevo mundo - Mundos Nuevos, 2013)
Following King Riroko’s “voluntary trip” to the Continent, in 1897, we propose to show that the Chilean State maintained a policy of deportation regarding rapanui authorities, which was against, and challenged, the colonial law. Such a policy would have concluded in 1916, when the parts involved arranged to manage dissent through alternative ways